1999
DOI: 10.1046/j.1432-1327.1999.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐affinity binding of fatty acyl‐CoAs and peroxisome proliferator‐CoA esters to glutathione S‐transferases

Abstract: Acyl-CoAs are present at high concentrations within the cell, yet are strongly buffered by specific binding proteins in order to maintain a low intracellular unbound acyl-CoA concentration, compatible with their metabolic role, their importance in cell signaling, and as protection from their detergent properties. This intracellular regulation may be disrupted by nonmetabolizables acyl-CoA esters of xenobiotics, such as peroxisome proliferators, which are formed at relatively high concentration within the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Various proteins such as albumin (Li et al, 2003b), sulfotransferases (Tulik et al, 2002), COX (Levoin et al, 2004), hepatocyte nuclear factor-4␣ (Hertz et al, 2001), and glucose-6-phosphate dehydrogenase (Asensio et al, 2007) have indeed been reported to interact with CoA thioester derivatives. It was found previously that long-chain saturated fatty acyl-CoAs and peroxisome proliferator-CoA thioesters exert high affinity toward GST (Silva et al, 1999). Our results provide another example of the ability of carboxylic acid-containing compound to bind to GST.…”
Section: Osbild Et Alsupporting
confidence: 64%
See 2 more Smart Citations
“…Various proteins such as albumin (Li et al, 2003b), sulfotransferases (Tulik et al, 2002), COX (Levoin et al, 2004), hepatocyte nuclear factor-4␣ (Hertz et al, 2001), and glucose-6-phosphate dehydrogenase (Asensio et al, 2007) have indeed been reported to interact with CoA thioester derivatives. It was found previously that long-chain saturated fatty acyl-CoAs and peroxisome proliferator-CoA thioesters exert high affinity toward GST (Silva et al, 1999). Our results provide another example of the ability of carboxylic acid-containing compound to bind to GST.…”
Section: Osbild Et Alsupporting
confidence: 64%
“…Furthermore, xenobiotic-SCoA metabolites were found to be much more reactive toward GSH than acylglucuronides (Olsen et al, 2002). Whereas Silva et al (1999) highlighted the absence of metabolism and hydrolysis of the thioester derivatives, interestingly, a transacylation reaction with GSH, enhanced in the presence of GST, was detected in the present study. MALDI-TOF MS analysis of KPF-SG obtained by enzymatic synthesis led to the identification of the expected ion MH ϩ m/z 544 (Fig.…”
Section: Interaction Of Ketoprofen Acylated Metabolites With Gstsupporting
confidence: 41%
See 1 more Smart Citation
“…There has been some recent evidence that PPARs can bind to and are activated by fatty acid-CoA esters [79,80]. Conversely, it has been shown that L-FABP also binds different fatty acid-CoA esters, albeit with lower affinity than fatty acids [53,81,82]. Furthermore, it was shown that overexpression of L-FABP in fibroblasts led to 2472 C. Wolfrum Intracellular fatty acid sensing increased targeting of a fluorescently labeled fatty acid-CoA ester or free fatty acids into the nuclear membrane and nucleoplasm [82], where it colocalized with PPARa.…”
Section: Fatty Acid Binding Proteinsmentioning
confidence: 99%